Impacto de la pandemia COVID-19 en la atención de pacientes con traumatismos atendidos en un hospital de Iquitos, 2019-2020 - Vásquez Fernandez, Viviana Patricia (2022)
Since the first COVID-19 cases were reported; this infection became a major global problem,1 which led to modifying the usual care strategies for other pathologies; including injuries of variable etiology. In the present descriptive retrospective study, the aim was to demonstrate the impact of the pandemic on the care of trauma patients treated at a hospital in Iquitos, comparing the care from the period from March to June 2019 and March to June 2020. The sample study comprised 311 patients from 2019 and 215 from 2020; mostly adult population, male and from the urban sector. A decrease in trauma care was observed during the confinement period. Vital signs remained within normal ranges in most patients; except for temperature, where cases of hypothermia were reported. Most of the patients stayed less than 1 day in the hospital; of which the highest percentage (88.6%) were treated during the pandemic. The most frequent mechanism of injury was due to a traffic accident in 46.1% before the pandemic, a percentage that was reduced to 28.8% the following year; the percentage of falls was equalized in the period of confinement. The type of injury that prevailed were blunt injuries; Limb and pelvic girdle injuries accounted for 86.6% of all reports. Non-serious injuries predominated in the study population; however, serious injuries (which in general represented 16.2%) comparatively increased in the period of confinement. A percentage of deaths of 0.4% was observed, all cases belonging to the period of confinement.